Criteria for chaotic transient oscillations in a model of driven buckled beams - Szemplińska-Stupnicka, Wanda; Tyrkiel, Elżbieta; Zubrzycki, Andrzej (Computer Assisted Methods in Engineering and Science, 2023)
The single-mode equation of motion of a class of buckled beams is considered, and the attention is focused on the phenomena of irregular, unpredictable transient oscillations which are observed in the region of the nonlinear resonance hysteresis. This type of transient motion may be dangerous in engineering dynamics, because it may last very long and is defined neither by the coefficient of damping nor by the magnitude of perturbation. While the steady-state chaotic motion has been studied extensively in the recent literature, little attention was paid to the chaotic transients. In the paper the criteria for transient chaos, i.e. the domain of the system control parameter values, where the chaotic transient motion can occur, are determined. The criteria are based on the theoretical concept of global bifurcations, and are estimated numerically.